Out-of-hospital Cardiac Arrest in the Republic of Crimea: Analysis of Epidemiology and Practice of Care - A. A. Birkun; L. P. Frolova; G. N. Buglak; S. S. Olefirenko (Неотложная медицинская помощь, 2020)
Introduction. Efficient organization of measures aimed at decreasing mortality from out-of-hospital cardiac arrest (OHCA) warrants a clear understanding of OHCA epidemiology and performance of the prehospital care system in such cases. The study was aimed at performing respective analysis and identifying the ways for improving prehospital management of OHCA in the Republic of Crimea.Material and methods. Annual data from the Crimean OHCA and Resuscitation Registry for 2018 were utilized. All OHCA cases attended by emergency medical services (EMS) with attempted cardiopulmonary resuscitation (CPR) were included, regardless of cardiac arrest etiology or patients’ age (n=419). For ensuring conformity and comparability of the study results, data collection and analysis were executed in correspondence with the statements of the Utstein recommendations.Results. The overall incidence of EMS-attended OHCA in the Republic of Crimea was 673.3 per 100,000 population per year, the incidence of OHCA with attempted CPR – 21.9 per 100,000 population per year, the proportion of CPR attempts out of all OHCA cases – 3.3%. Mean patient age was 66.9 years, and 52.7% were male. The etiology was cardiac in 42.5% cases. In 71.8% cases OHCA was witnessed by EMS, in 25.5% – by a bystander before EMS arrival. Bystanders initiated CPR in 5.7% cases. The initial rhythm was asystole in 80.4% of all cases. When excluding EMS-witnessed cases, the mean EMS response time was 13 min. 5.0% patients had a sustained return of spontaneous circulation at hospital admission. Survival was associated with lower EMS response time (p=0.027), administration of shock (p<0.001) and advanced airway management with endotracheal tube or laryngeal mask (p=0.047).Conclusion. High incidence of OHCA, low rates of CPR commencement and low rates of survival from OHCA in the Republic of Crimea determine the necessity of implementing a comprehensive program to improve prehospital care in the region. Considering the critical relevance of early intervention in OHCA and the revealed low bystander CPR rate, the measures for involving community into the process of prehospital care should form the basis of this program.